Studi Deskriptif mengenai Coping Stress pada Ibu yang Memiliki Anak dengan Autism Sebuah Penelitian di Sekolah â€œXâ€ Bandung - Erika Armajayanthi; Evany Victoriana; Kangga Liedia Ayu (Humanitas (Jurnal Psikologi), 2017)
Having a child with autism can make a mother stress so that mothers need to relieve stress using coping stress. This study uses the theory of coping stress of Lazarus & Folkman (1984) to describe the coping stress used by mothers of children with autism in Schools "X". The number of participants of this study are 17 mothers age 27 - 55. All the participants were asked to fill out a questionnaire called Ways of Coping, that has been modified and adapted to the characteristics of the participants. Scores obtained can give descriptions about the form and component of coping used by participants. Items using a Likert scale, with the scaling interval. Counting the validity using SPSS version 22, using Pearson Correlation. From the calculation, there is one item that is discarded. Calculation reliability using software SPSS version 22, using Cronbach Alpha. Based on the results, the reliability of "Ways of Coping" is 0.875, which means it has high reliability. Based on statistical data, of the 17 participants, 9 participants mostly use problem focused coping, 7 participants mostly use emotional focused coping, andÂ  one participant use both forms of coping in a balanced manner. The conclusion is, most participants use problem focused coping more than emotional focused coping.Â Keywords: mother, autism, stress, coping stress.